Factors Affecting The Local Taxes Revenue By Provincial Governments In Indonesia - Zulfi, Muhammad Ramadhan; Wijaya, Suparna (WIM Solusi Prima, 2024)
This study aims to investigate the influence of regional gross domestic product (GDP), population size, and the poverty rate on the local tax revenues of Indonesian provincial governments. Secondary data from the publications of the Central Statistics Agency (Badan Pusat Statistik) covering a 5-year period from 2016 to 2020 were utilized for this research. The study focuses on 34 provinces in Indonesia. The research employs panel data regression with the panel-generalized least squares model. The findings indicate that regional GDP has a positive and significant impact on the local tax revenues of provincial governments. An increase in the population size also positively and significantly affects the local tax revenues. Conversely, a rise in the percentage of the population living in poverty has a negative and significant effect on local tax revenues of provincial governments. The simultaneous influence of regional GDP, population size, and the poverty rate on local tax revenues is also significant. To promote higher local tax revenues, the government should encourage economic growth in the regions and invest in enhancing the quality of human resources. This approach would lead to increased regional GDP and population, thereby boosting local tax revenues. Furthermore, efforts to reduce poverty levels would raise consumption and income among the population, ultimately contributing to increased local tax revenues.